Cellular and Molecular Pathways of COVID-19 and Potential Points of Therapeutic Intervention - Hussman, John P. (Frontiers in Pharmacology, 2020)
With the objective of linking early findings relating to the novel SARS-CoV-2 coronavirus with potentially informative findings from prior research literature, and to promote investigation toward therapeutic response, a coherent cellular and molecular pathway is proposed for COVID-19. The pathway is consistent with a broad range of observed clinical features and biological markers, and captures key mediators of pathophysiology. In this proposed pathway, membrane fusion and cytoplasmic entry of SARS-CoV-2 virus via ACE2 and TMPRSS2-expressing respiratory epithelial cells, including pulmonary type-II pneumocytes, provokes an initial immune response featuring inflammatory cytokine production coupled with a weak interferon response, particularly in IFN-lambda-dependent epithelial defense. Differentiation of non-classic pathogenic T-cells and pro-inflammatory intermediate monocytes contributes to a skewed inflammatory profile, mediated by membrane-bound immune receptor subtypes (e.g. FcgRIIA) and downstream signaling pathways (e.g. NF-kB p65, p38 MAPK), followed by chemotactic infiltration of monocyte-derived macrophages and neutrophils into lung tissue. Endothelial barrier degradation and capillary leakage contribute to alveolar cell damage. Inflammatory cytokine release, delayed neutrophil apoptosis, and NETosis contribute to pulmonary thrombosis and cytokine storm. These mechanisms are concordant with observed clinical markers in COVID-19, including high expression of inflammatory cytokines on the TNF-alpha/IL-6 axis, elevated neutrophil-to-lymphocyte ratio (NLR), diffuse alveolar damage via cell apoptosis in respiratory epithelia and vascular endothelia, elevated lactate dehydrogenase (LDH) and C-reactive protein (CRP), high production of neutrophil extracellular traps (NETs), depressed platelet count, and thrombosis. Although certain elements are likely to be revised as new findings emerge, the proposed pathway suggests multiple points of investigation for potential therapeutic interventions. Initial candidate interventions include prophylaxis to augment epithelial defense (e.g. AT1 receptor blockade, Type III and Type I interferons, melatonin, calcitriol, camostat, lopinavir) and to reduce viral load (e.g. remdesivir, ivermectin, emetine, Abelson kinase inhibitors, dopamine D2 antagonists, selective estrogen receptor modulators). Additional interventions focus on tempering inflammatory signaling and injury (e.g. dexamethasone, doxycycline, Ang1-7, estradiol, alpha blockers, DHA/EPA, pasireotide), as well as inhibitors targeted toward molecular mediators of the maladaptive COVID-19 immune response (e.g. IL-6, TNF-alpha, IL-17, JAK, CDK9).